FAKTOR-FAKTOR YANG MEMENGARUHI PENYERAPAN ANGGARAN SATUAN KERJA PERANGKAT DAERAH DI PEMERINTAH KABUPATEN SITUBONDO - Widianingrum, Desika; Kustono, Alwan Sri; Suryaningsih, Ika Barokah (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2017)
Abstract: Disproportionate budget absorption is a common issue in managing local government finances. This study aimed to identify factors that affect the absorption level of the budget managed by theworking units (SKPD) in Situbondo Regency Government. The sample was collected using purposive sampling method and consisted of 200 respondents, i.e., the Spending Treasurers, the Committing Officers, and the Financial Administration Officers. Data were analyzed using exploratory factor analysis. The results show that there are six factors that affect the budget absorption, namely: (1) planning factor that explains the variance of all items amounted to 24.31%; (2) goods/services procurement factor that explains the variance of all items amounted to 11.10%; (3) regulation factor that explains the variance of all items amounted to 8.57%; (4) internal factor that explains the variance of all items amounted to 7.03%; (5) administration factor that explains the variance of all items at 5.92%; and (6) human resources factor that explains the variance of all items by 5.56%. The six factors have the variance of 62.49% in affecting the budget absorption, while the remaining 37.51% is explained by the other factors. Keywords: Budget Absorption, Exploratory Factor Analysis.